Influence of additives on polycarbonate/acrylonitrile-butadiene -styrene blending for fused deposition modeling. Issue 1 (February 2020) - Chen, Y W; Yin, Y; Feng, L; Ling, X; He, J K; Lai, W W; Wang, Y
Abstract: This study aimed to investigate the use of polycarbonate (PC), acrylonitrile-butadiene-styrene (ABS), PC/ABS/maleinized acrylonitrile-butadiene-styrene copolymer (ABS-g-MAH) composite, PC/ABS/methyl methacrylate-butadiene-styrene (MBS) composite, and PC/ABS/organic montmorillonite composite for fused deposition modeling experiments and compare their mechanical properties. The tensile test results of specimens printed with different orientations revealed that PC/ABS compatibilized by 7% MBS exhibited the highest tensile elongation of the samples built in a horizontal orientation. Moreover, PC/ABS compatibilized by 6% ABS-g-MAH showed the greatest tensile strength between the three composite specimens printed with horizontal orientations. The notch impact test results revealed that PC/ABS/ABS-g-MAH and PC/ABS/MBS composite specimens printed with horizontal and vertical orientations were much stronger than the other systems.